2013
DOI: 10.1371/journal.pone.0063062
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidant-Scavenging Abilities in the Oral Cavity May Be Regulated by a Collaboration among Antioxidants in Saliva, Microorganisms, Blood Cells and Polyphenols: A Chemiluminescence-Based Study

Abstract: Saliva has become a central research issue in oral physiology and pathology. Over the evolution, the oral cavity has evolved the antioxidants uric acid, ascorbate reduced glutathione, plasma-derived albumin and antioxidants polyphenols from nutrients that are delivered to the oral cavity. However, blood cells extravasated from injured capillaries in gingival pathologies, or following tooth brushing and use of tooth picks, may attenuate the toxic activities of H2O2 generated by oral streptococci and by oxidants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 44 publications
1
28
4
Order By: Relevance
“…The cocktail alone showed no decrease in luminescence with time. Saliva (at 15 μL), in agreement with a previous report (Ginsburg et al, ), and FPP (up to 10 mg), each one alone, had a very modest effect, while combinations of FPP (2–10 mg) and saliva (15 μL) had a significant quenching effect, indicating the ability of FPP in saliva to decompose H 2 O 2 and hydroxyl radicals generated by the cocktail. Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The cocktail alone showed no decrease in luminescence with time. Saliva (at 15 μL), in agreement with a previous report (Ginsburg et al, ), and FPP (up to 10 mg), each one alone, had a very modest effect, while combinations of FPP (2–10 mg) and saliva (15 μL) had a significant quenching effect, indicating the ability of FPP in saliva to decompose H 2 O 2 and hydroxyl radicals generated by the cocktail. Fig.…”
Section: Resultssupporting
confidence: 91%
“…We have previously suggested that the antioxidant status in the oral cavity might be affected by interactions among antioxidants of the saliva, the oral microbial flora, blood elements extravasated from injured capillaries and polyphenols from nutrients (Ginsburg et al, 2013). The antioxidants may counteract toxic oxidants that include peroxides, thiocyanous acid (Grisham and Ryan, 1990) and oxidants generated by activated neutrophils (Battino et al, 1999) and bacteria (Okahashi et al, 2014), which accumulate in infectious sites in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with worse periodontal condition tended to have increased oxidative injury to periodontal tissue. Recently, total levels of ROS or antioxidant activity were determined using fluorescence analysis (Tsutsumi et al 2012), chemiluminescence (Ginsburg et al 2013), and absorptiometry (Tamaki et al 2011). However, these analyses quantify antioxidant activities against nonspecific ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells coated by polyphenols, further act with salivary low molecular weight antioxidants (LMWA) to enhance the scavenging of reactive oxygen species, both acting as solubilizers of polyphenols making them antioxidants that are more effective. [18] Deficiency of beta carotene can lead to periodontal destruction. Prostaglandin inhibitory effect of alpha tocopherol contributes in reducing periodontal inflammation.…”
Section: Mode Of Actionmentioning
confidence: 99%